2017
DOI: 10.3389/fmicb.2017.01851
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Exploitation of CRISPR Loci in Bifidobacterium longum

Abstract: Diverse CRISPR-Cas systems provide adaptive immunity in many bacteria and most archaea, via a DNA-encoded, RNA-mediated, nucleic-acid targeting mechanism. Over time, CRISPR loci expand via iterative uptake of invasive DNA sequences into the CRISPR array during the adaptation process. These genetic vaccination cards thus provide insights into the exposure of strains to phages and plasmids in space and time, revealing the historical predatory exposure of a strain. These genetic loci thus constitute a unique basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
52
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 78 publications
12
52
2
1
Order By: Relevance
“…In many incomplete sets, we observed the occurrence of transposases, which have been previously observed in CRISPR loci (41,42). The coexistence of several CRISPR-Cas systems in the same genome has been previously described in several gut lactobacilli and bifidobacteria (41,43), as well as in Streptococcus thermophilus starter cultures (44,45). Overall, we determined widespread occurrence of CRISPR-Cas systems in L. crispatus, notably complete type I-E systems ( Fig.…”
Section: Resultssupporting
confidence: 74%
“…In many incomplete sets, we observed the occurrence of transposases, which have been previously observed in CRISPR loci (41,42). The coexistence of several CRISPR-Cas systems in the same genome has been previously described in several gut lactobacilli and bifidobacteria (41,43), as well as in Streptococcus thermophilus starter cultures (44,45). Overall, we determined widespread occurrence of CRISPR-Cas systems in L. crispatus, notably complete type I-E systems ( Fig.…”
Section: Resultssupporting
confidence: 74%
“…Previous studies have identified phylogeny of Cas1 as one of the key factors to subtype classification [68]. Additionally, the tree showed the aggregation of the Cas1 sequences was on the same big branch according to subtype IE, IIA, and IIIA, which was roughly the same as the phylogeny of the DR sequence, confirming the trend of co-evolution of components in the immune system [29]. The most frequent repeats were usually defined as typical repeats.…”
Section: Discussionsupporting
confidence: 61%
“…The Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) region and the CRISPR-related protein (Cas) were predicted using the CRISPR CasFinder [28], and neighbor-joining trees based on Cas protein were built [29]. The sequence of conserved direct repeats (DRs) were visualized by WebLogo [30].…”
Section: Crispr-cas Identification and Characterizationmentioning
confidence: 99%
“…CRISPR-Cas Type II immune systems (II-A, II-C) are fairly rare and occur in only 5% of bacteria, but they occur at a much higher frequency in the Bifidobacterium genus [24]. Characterization of Type II elementsmay provide opportunities to use the molecular genome-editing tool for the development of next-generation probiotic bacteria [25]. The B. gallinarum CACC 514 CRISPR-Cas system may also provide a platform for various potential biotechnological and ecological uses as probiotic bacteria.…”
Section: Crisprmentioning
confidence: 99%